Qualitative Study: High-Risk Sexual Behavior and Prevention of STD and HIV/AIDS Among Female Sellers at Sindhu Market Sanur, Bali - Luh Gede Pradnyawati (Warmadewa University, 2019)
Previous Research showed that having multiple sex partners was a risk-taking behavior that caused the susceptibility of getting STD and HIV/AIDS among female sellers in the market. However, this high-risk behavioral pattern has not been explained. The aim of this study was to understand the pattern of risky sexual behavior and the pattern of prevention of STD and HIV/AIDS among female sellers. This study was conducted by qualitative method, and the respondents were chosen by purposive sampling method. Twenty female sellers in Sindhu Market aged 18 to 45 years old who were sexually active agreed to be the key informants for this study. Data on risky sexual behaviours and pattern of prevention of STD and HIV/AIDS were collected by in-depth interview and were analysed thematically. Results showed thath 7 out of 20 female sellers conducted risky sexual behavior by doing premarital sex and having multiple sex partners without using condom. Most of the informants used vaginal wash and betel soap to prevent STD and HIV/AIDS, and some even checked themselves to the health center for medication.